The Growth Explains its Reasons Itself: From the Retrospect of Bangladesh Economy - Akter, Farzana; Rahman, A.S.M. Habibur (Asian Business Review, 2015)
Bangladesh, a country with a potential economic growth had a rich agro-based economy before & after its independence. Being one of the most heavily populated countries of the world, it had to face several development challenges. Accelerated growth was just a demand of time that was pushing the whole economy towards Industrial & Service Sector where growth could be achieved swiftly. This research was performed to portray the structural transition in the economy of Bangladesh after independence. GDP at a constant price was used to represent The Growth of the economy. Step by step, the decomposition method was used to split GDP to the bottom & to get the most influential sectors & sub-sectors and their recent trends. The findings from decomposition method were supported by linear regression.  A detail & authentic dataset (42 years) was used to clarify the transition to the economy.JEL Classification Code: O14, O53
Keywords: Growth; GDP; Transition; Bangladesh; Agriculture; Industry; Service